Symptomatic osteochondroma of the chest wall - Gulan Maree; Samer Rajab; Mohammad Ahmad Almahmod Alkhalil (Elsevier, 2022)
Hereditary multiple exostosis (HME) is a rare skeletal disease in children characterized by the formation of benign tumors near bone growth plates. The metaphysis of long bones is most commonly affected, with a predilection for the distal femur, proximal tibia, and proximal humerus. It is uncommonly found on the scapulae's vertebral borders, iliac crests, and ribs. We present a 2.5-year-old child with a history of several tumors on his body, the largest of which measured 95 × 55 × 40 mm on the 8th rib on the right side of the chest wall. This tumor was painful, but there were no injuries to the intrathoracic contents. HME was confirmed based on clinical examination, family history, radiographic examination, and histological examination. It was completely excised along with another painful tumor on the right scapula. The child was discharged in good health after 4 days postoperatively without any problems with follow-up. Because the risk of malignant transformation increases as these tumors grow in size and cause pain, especially at this age, surgical removal was required.